Warped - Red Hot Chili Peppers; Rubin, Rick; Warner Bros Records (United States : Warner Bros Records, 1995)
Contains the single taken from the album One Hot Minute.
CD 1 : Warped (edit) / (4:19)
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English